Studi Pengunaan Pakan Pelet Hasil Formulasi dari Bahan Baku Nabati Untuk Meningkatkan Pertumbuhan Benih Ikan Gurami (Osphronemusgouramy) - Munawar Khalil; Zahnila Zahnila; Prama Hartami (Berkala Perikanan Terubuk, 2015)
The study aimed to determine the effect of formulated feed from different vegetable sources onto growth of gouramy fingerling (Osphronemus gouramy). The method used a non factorial completely randomized design with five treatments and three replications, namely A: commercial feed (control), B: formulated feed of Moringa, C: formulated feed Gliricidia, D: formulated feed ofCentella asiatica and E: formulated feed of three vegetable mixture. The results showed that formulated feed from different vegetable sources gave highly significant effect on growth of length (1,025± 0,126 cm in average) and weight1,133 ± 0,212 gram in average), feed conversion ratio (6,96±0,32 in average)and the response of fish to feed (25,61±0,65 minutes), which was Fcount > F table. The highest value on growth and feed conversion ratio was obtained in treatment B, whereas, the best response of fish to formulated feedwas obtained in treatment A (commercial feed). Furthemore, formulated feed also provided survival rate of gouramy (Osphronemus gouramy) relatively well.